Performance measurement in transport sector analysis - Išoraite, Margarita (Transport, 2004)
The article analyses the following issues: 1. Performance measurement in literature. The performance measurement has an important role to play in the efficient and effective management of organizations. Kaplan and Johnson highlighted the failure of the financial measures to reflect changes in the competitive circumstances and strategies of modern organizations. Many authors have focused attention on how organizations can design more appropriate measurement systems. Based on literature, consultancy experience and action research, numerous processes have been developed that organizations can follow in order to design and implement systems. Many frameworks have been proposed that support these processes. The objective of such frameworks is to help organizations define a set of measures that reflect their objectives and assess their performance appropriately. 2. Transport sector performance and its impacts measuring. The purpose of transport measurement is to identify opportunities enhancing transport performance. Successful transport sector management requires a system to analyze its efficiency and effectiveness as well as plan interventions if transport sector performance needs improvement. Transport impacts must be measurable and monitorable so that the person responsible for the project intervention can decide when and how to influence them. Performance indicators provide a means to measure and monitor impacts. These indicators essentially reflect quantitative and qualitative aspects of impacts at given time and places. 3. Transport sector output and input. Transport sector inputs are the resources required to deliver transport sector outputs. Transport sector inputs are typically: human resources, particularly skilled resources (including specialists consulting inputs); technology processes such as equipment and work; and finance, both public and private. 4. Transport sector policy and institutional framework; 5. Cause – effect linkages; 6. Alternatives analysis. The numerous courses of action could be taken to improve performance. However, due to limited resources choices have to be made. This requires prioritizing. First Published Online: 27 Oct 2010